Development of kinetics model for torrefaction of empty fruit bunch from palm oil waste - Nur Hazirah Huda, Mohd Harun; Noor Asma Fazli, Abdul Samad; Suriyati, Saleh (Elsevier Ltd, 2017)
Torrefaction is a thermal conversion method widely used for enhancing the properties of biomass. Usually this process is conducted under an inert atmosphere within a temperature range of 200°C - 300°C with residence time up to 60 minutes. During the torrefaction process, biomass is thermally decomposed thus resulted in biomass weight loss which is known as an anhydrous weight loss (AWL). As the properties of biomass are highly dependent on the AWL, therefore it is important to predict the reaction kinetics which will enable to describe the thermal degradation of the respective biomass for achieving the desired properties of torrefied biomass. In this study, the kinetic parameters of empty fruit bunch (EFB) from palm oil waste torrefied at 240°C and 270°C are predicted by applying two different kinetic models namely Di Blasi-Lanzetta Model and Rousset Model for both heating and isothermal phases. For Di Blasi-Lanzetta Model, the kinetic parameters are estimated based on the degradation of EFB into intermediate compound and char whereas kinetic parameters for Rousset Model are predicted based on the degradation of three main constituents of EFB which consists of lignin, cellulose and hemicellulose. All kinetic parameters are estimated according to Arrhenius law and fitted to the experimental result. The result shows that AWL estimation using kinetic parameters predicted from both models are in a good agreement with the experimental result and thus applicable to represent AWL of EFB torrefaction. In conclusion, Di Blasi-Lanzetta Model is more relevant to represent real torrefaction in comparison to the Rousset because of its ability to provide detailed information for the evolution of solid and volatile products during torrefaction.